Challenges and Opportunities for Implementing Green HRM in Management Source Human Resources in Higher Education - Sugiharto, Vebri; Muhammad Ardiansyah (Al-Qalam Institue, 2025)
Green Human Resource Management (Green HRM) integrates human resource practices with environmental sustainability goals. Higher education institutions, as educational institutions that influence future generations , have a crucial role to play in adopting green human resource management . This article aims to identify the challenges and opportunities for implementing green human resource management in higher education, as well as to provide recommendations for more sustainable human resource management. This research method uses a qualitative approach with a literature review approach. This approach is a comprehensive survey of scientific sources on a specific topic. The literature review provides a critical evaluation of these sources, including substantive findings as well as theoretical and methodological contributions to a specific topic. The results of the study indicate that despite challenges such as resistance to change and budget constraints, opportunities for implementing green human resource management remain , such as improving institutional image and operational efficiency, which can have long-term positive impacts. This study proposes stronger policies to support sustainability in higher education environments.